PENGARUH PARTISIPASI DALAM PENYUSUNAN ANGGARAN TERHADAP KINERJA MANAJERIAL DENGAN KOMITMEN ORGANISASI, BUDAYA ORGANISASI DAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING (Studi Kasus pada Rumah Sakit Umum Daerah dr. Moewardi di Surakarta) - Sukma Romadhona Agusrini, Djoko Kristianto & Muhammad Rofiq Sunarko (Universitas Slamet Riyadi, 2016)
The purpose of this study were: 1) analyze the significance of the effect of budget participation, organizational commitment, organizational culture and work motivation on managerial performance. 2) analyze the significance of the effect of budget participation on organizational commitment, organizational culture and work motivation. 3) analyze whether the interaction between the budgeting and organizational commitment that serves as an intervening variable affecting managerial performance. 4) analyze whether the interaction between budgeting with the culture of the organization that serves as an intervening variable affecting managerial performance. 5) analyze whether the interaction between budgeting with motivation serves as an intervening variable affecting managerial performance. The research method used survey method, the type of data used quantitative and qualitative data, the data source used primary data and secondary data. The population in this study are all managers and heads of sections involved in the budgeting process at the Regional General Hospital (Hospital) dr. Moewardi in Surakarta, as many as 55 people, the number of samples used were 38 respondents with sampling techniques using census method. Methods of data collection using questionnaires. Data analysis technique used to test the validity, reliability test, classic assumption test, path analysis. In conclusion: 1) Variable participation budgeting, organizational commitment, organizational culture and work motivation have a significant effect on managerial performance. 2) Participation budgeting significant effect on organizational commitment, organizational culture and work motivation. 3) Organizational commitment does not moderate the effect of budget participation on managerial performance. 4) The organizational culture does not moderate the effect of budget participation on managerial performance. 5) Work motivation does not moderate the effect of budget participation on managerial performance.Keywords: participation budgeting, organizational commitment, organizational culture, motivation and managerial performance